2013
DOI: 10.1007/s00392-013-0610-1
|View full text |Cite
|
Sign up to set email alerts
|

Does cirrhotic cardiomyopathy exist? 50 years of uncertainty

Abstract: Subtle abnormalities of cardiac structure or function are often identified in patients with liver cirrhosis and have been termed cirrhotic cardiomyopathy. However, in the absence of a precise definition, its diagnosis remains a challenge. Cardiac dysfunction in patients with cirrhosis can often be attributed to concomitant diseases such as hypertension, ischaemic heart disease or excess alcohol consumption in many patients. Further research is required to identify the existence, origin and importance of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…56,87 GLS can detect contractile dysfunction earlier than LV EF, which mainly reflects radial fibers dysfunction occurring at later stages. 28,53,88 In cirrhotic patients having low afterload, strain results might be normal at rest; however, even very early stages of myocardial impairment can be revealed by stress testing. 87 In a study using the assessment of GLS by cardiovascular magnetic resonance, Sampaio et al found similar systolic function at rest but impaired myocardial deformation during stress test using a low to moderate dose of dobutamine in cirrhotic patients compared with healthy controls.…”
Section: Systolic Functionmentioning
confidence: 99%
“…56,87 GLS can detect contractile dysfunction earlier than LV EF, which mainly reflects radial fibers dysfunction occurring at later stages. 28,53,88 In cirrhotic patients having low afterload, strain results might be normal at rest; however, even very early stages of myocardial impairment can be revealed by stress testing. 87 In a study using the assessment of GLS by cardiovascular magnetic resonance, Sampaio et al found similar systolic function at rest but impaired myocardial deformation during stress test using a low to moderate dose of dobutamine in cirrhotic patients compared with healthy controls.…”
Section: Systolic Functionmentioning
confidence: 99%
“…Hepatic disease may likewise cause anemia, which also affects cardiac structure and function. Therefore, the relationship between cirrhosis and cardiac disease cannot be assured (77).…”
Section: Controversial Issuesmentioning
confidence: 99%
“…33 In addition to hemodynamic changes, a decline in cardiac function termed cirrhotic cardiomyopathy has also been described. 34 Although there remains no consensus definition, 35 it should be considered in the setting of diastolic and systolic dysfunction, especially in cases where diastolic dysfunction precedes systolic dysfunction. 36 Cirrhotic cardiomyopathy can be associated with a prolonged QT interval and can lead to an increased risk of ventricular arrhythmias/sudden cardiac death.…”
Section: Cardiovascularmentioning
confidence: 99%